IMPLEMENTATION OF PEACEBUILDING EDUCATION IN EDUCATIONAL INSTITUTIONS OF UKRAINE - Olena Akilina; Alla Panchenko; Anastasiia Horozhankina (Borys Grinchenko Kyiv Metropolitan University, 2023)
The article deals with the issue of introducing peacebuilding education in domestic educational institutions. The authors determine that the effective implementation of peacekeeping education requires certain organizational transformations, which should include: changing the management system of an educational institution, which involves the use of transformational leadership, as well as involving all participants in the educational process in decision-making; forming a favorable and safe educational environment based on the values of peacekeeping education; creating an "aligned structure" of an educational institution that will promote trust and cooperation between participants in the educational process; correct goal setting in the educational system of an educational institution, which should include the formation of socially significant goals and prospects for joint activities for the introduction of peacekeeping education. The authors of the article also draw attention to the important role of teachers in the implementation of peacekeeping education. In the context of russian aggression against Ukraine, the role of a teacher as a defender of Ukrainian culture and a peacemaker is growing. It must resist russian propaganda and form the right values in children and young people, in particular the values of nonviolent communication and mutual understanding. The authors paid special attention to the Ukrainian language, which, has there is a huge potential to become an effective tool for peacekeeping education. In within the framework of this study, a questionnaire was used, which allowed us to determine the opinion of teachers undergoing training in the educational and professional program "managing an educational institution (by level)" at the Borys Grinchenko Kyiv University regarding the importance of the Ukrainian language for peacekeeping education.